Degradation behavior of porous polymeric scaffold - Neo, Jia Ling (2009)
Scaffolds function as the body’s extra cellular matrix (ECM) in vitro, providing the necessary support for cells to proliferate, until they are replaced. Porosity, pore size, chemical composition, and degradation rate are some important consideration of a scaffold. The chitosan-gelatin hybrid scaffold was chosen for investigation due to its biocompatibility and versatile properties. In this report, the choices of parameters in fabricating the scaffolds were justified through preliminary studies. The freezing and lyophilizing method was selected to construct the hybrid scaffold, with a freezing temperature of -80oC. Analysis of the scaffolds were divided into two groups: (I) chitosan is to gelatin w/v % of 0:3, 1:3, 2:3 and 3:3, (II) chitosan is to gelatin w/v % of 2:0, 2:3, 2:7 and 2:10. Results showed that higher concentrations of gelatin led to the formation of scaffolds with closed pores. The porosity of the scaffolds was also dependent on the content of gelatin and chitosan, with P≤0.05 for both groups. Finally, degradation analysis was performed by measuring the weight loss of the scaffolds for a period of 23 days. These models may serve as predictive tools for hybrid scaffolds of different concentrations, fabricated using the same method as described in this report.